2012
DOI: 10.1597/09-047
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement in Individuals with Cleft: A Population-Based Register Study

Abstract: This study clearly indicates that adolescents with cleft lip and/or palate in Sweden experience significant deficits in their educational achievements in compulsory school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 26 publications
5
104
3
1
Order By: Relevance
“…These findings are consistent with those from earlier populationbased studies. 13,14 Our study extends these findings to more rigorous and direct methods of assessment of academic achievement, controlling for several potential demographic and socioeconomic confounders.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These findings are consistent with those from earlier populationbased studies. 13,14 Our study extends these findings to more rigorous and direct methods of assessment of academic achievement, controlling for several potential demographic and socioeconomic confounders.…”
Section: Discussionsupporting
confidence: 53%
“…[8][9][10][11][12] However, population-based investigations are rare, and most studies have included small, clinicbased patient samples. The only 2 existing population-based studies relied on indirect measures of academic performance, including classroom grades and graduation rates from compulsory schools in Sweden 13 and frequency of special education placement in Atlanta, Georgia. 14 Both studies suggested poor academic functioning among individuals with clefts.…”
mentioning
confidence: 99%
“…Results of the two behavioral hearing tests in the current research suggest children with cleft palate have more difficulty in auditory processing tasks than children with other cleft types. Differences among cleft types in academic achievement, such as more negative performance in children with CP and better performance in children with CL, were previously reported in the literature [27]. However, research evidence to explain variation between cleft groups is sparse.…”
Section: Performance In Mappid-n Test For Children With Cp and Bclpmentioning
confidence: 89%
“…There are also data suggesting that people with cleft lip and/or palate have lower educational attainment and reduced life expectancy. 1,2 The evidence to inform clinical care for children with cleft lip and/or palate is limited. Much clinical practise is supported by case reports or case series.…”
Section: The Importance Of Evidence Informing Service Rationalisationmentioning
confidence: 99%